KH. Abu Dardiri (1895-1967): Inspirator Persyarikatan Muhammadiyah di Kabupaten Purbalingga - Fathony, Bimba Valid (RUSYDIAH: Jurnal Pemikiran Islam, 2023)
This research aims to explain K.H. Abu Dardiri is an inspirational figure for the Muhammadiyah Association in Purbalingga Regency with a historical approach. The sub-discussion in this research consists of, the history of the founding of Muhammadiyah in Purbalingga Regency, the life history of K.H. Abu Dardiri, The legacy and progress of K.H. Abu Dardiri in Purbalingga Regency, and the exemplary role of K.H. Abu Dardiri as an inspirational figure for the Muhammadiyah Association in Purbalingga Regency.. The method used by researchers in compiling this research is the historical method. A brief conclusion to this research is, K.H. During his lifetime, Abu Dardiri gave many dedications to the people and nation, especially to the Muhammadiyah Association. When Muhammadiyah Purbalingga was first founded, he was elected chairman. The success of the Muhammadiyah Association in Purbalingga Regency cannot be separated from its successors who inherited the spirit and militancy of K.H. Abu Dardiri as an inspirational figure.